2022
DOI: 10.1186/s12913-022-07582-6
|View full text |Cite
|
Sign up to set email alerts
|

Intervention by a clinical pharmacist carried out at discharge of elderly patients admitted to the internal medicine department: influence on readmissions and costs

Abstract: Background Patient education on pharmacological treatment could reduce readmissions. Our objective was to carry out a pharmacist intervention focused on providing information about high-risk medications to chronic patients and to analyse its influence on readmissions and costs. Methods A single-centre study with an intervention group and a retrospective control group was conducted. The intervention was carried out in all polymedicated patients ≥ 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…First, telephone-based interventions were generally found to be costeffective in the studies included in this review. That is, five out of the seven phone-based studies revealed the economic benefits of the phone interventions [32,33,35,36,38]. In the other two telephone-based studies by Pyne et al and Painter et al [19,20], the authors concluded that the interventions were not cost-effective because the ICERs of the interventions were higher than the conventionally cited WTP thresholds of USD 50,000-USD 150,000/QALY.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…First, telephone-based interventions were generally found to be costeffective in the studies included in this review. That is, five out of the seven phone-based studies revealed the economic benefits of the phone interventions [32,33,35,36,38]. In the other two telephone-based studies by Pyne et al and Painter et al [19,20], the authors concluded that the interventions were not cost-effective because the ICERs of the interventions were higher than the conventionally cited WTP thresholds of USD 50,000-USD 150,000/QALY.…”
Section: Discussionmentioning
confidence: 95%
“…Of these 14 studies, pharmacists used a telephone-based intervention in seven. Five out of the seven studies reported the economic benefits of the phone interventions [32,33,35,36,38]. Dehmar et al's CEA study revealed that home blood pressure monitoring and pharmacist case management improved hypertension care in a cost-effective manner [35].…”
Section: Telephone-based Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…While formalized AMS education or certification is not standard during training for IM pharmacists, they regularly manage antimicrobials for urinary tract infections, lower respiratory tract infections, skin and skin structure infections, and bloodstream infections. While the overall utility of IM pharmacists as a part of the health care team is described within the literature, less is documented about their impact on AMS initiatives and any barriers they encounter to their interventions 16,21–24 . This study was conducted to characterize AMS interventions made by IM pharmacists and their trainees.…”
Section: Introductionmentioning
confidence: 99%
“…While the overall utility of IM pharmacists as a part of the health care team is described within the literature, less is documented about their impact on AMS initiatives and any barriers they encounter to their interventions. 16,[21][22][23][24] This study was conducted to characterize AMS interventions made by IM pharmacists and their trainees.…”
Section: Introductionmentioning
confidence: 99%